(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article studies the translation of behavioral verbs—verbs that describe human actions, attitudes, and social interactions—poses significant linguistic challenges due to semantic variability, syntactic differences, and cultural nuances. This study investigates these challenges by analyzing a bilingual corpus alongside semi-structured interviews with professional translators. The research identifies key obstacles such as polysemy, verb valency mismatches, and pragmatic shifts that complicate direct equivalence between source and target languages. Translators commonly employ adaptive strategies including contextual modulation, compensation, and specification to preserve intended meaning and communicative effect.